FOCUSED CRAWLING TECHNIQUES (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The need for more and more specific reply to a web search query has prompted researchers to work on focused web crawling techniques for web spiders. Variety of lexical and link based approaches of focused web crawling are introduced in the paper highlighting important aspects of each.